Electronics, communications and networks IV : proceedings of the 4th International Conference on Electronics, Communications and Networks, 12-15 December 2014, Beijing, China /: proceedings of the 4th International Conference on Electronics, Communications and Networks, 12-15 December 2014, Beijing, China. (2015) - Unknown
No abstract available